Revealing the impact of the competence of enterprises' personnel on energy-saving technological changes - Lesinskyi, Valentyn; Yemelyanov, Olexandr; Zarytska, Oksana; Petrushka, Tetyana; Myroshchenko, Nataliia (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates competence of enterprise personnel in the development and implementation of energy-saving technological change projects. The task addressed is to identify the impact of these competences on energy-saving technological change. A grouping of competences in the implementation of energy-saving technological change projects was advanced. Using the constructed three-level model of assessing the impact of factors on energy-saving technological change at enterprises, the place of personnel competences among these factors was established. The methodological principles of assessing the impact of personnel competence on energy-saving technological change at enterprises were improved by designing a toolkit for indirect and direct assessment of the specified impact. Such an assessment, among other things, provides for the establishment of reserves for reducing obstacles to the implementation of energy-saving technologies by increasing personnel competence. The designed toolkit was tested using data from 34 enterprises in Ukraine. In particular, it was found that the transition of enterprises with a low level of personnel competence to the class of companies with medium and high levels of such competence, respectively, would lead to an expected increase in average energy efficiency by 35.89% and 84.15%. At the same time, eliminating obstacles caused by insufficiently high competence of the personnel could make it possible to reduce the average overall level of such obstacles by type of economic activity for enterprises from 35.48% to 54.17%. The proposed toolkit is suitable for use by enterprises of all types of economic activity when assessing reserves for increasing energy efficiency by improving employee competence